Complete denture wearing and fractures among edentulous patients treated in university clinics - Takamiya, Aline S.; Monteiro, Douglas R.; Marra, Juliê; Compagnoni, Marco A.; Barbosa, Debora B. (Wiley, 2012)
Objective: The prevalence of wearing and fracture of complete dentures was evaluated among edentulous patients treated in two dental schools in Brazil. Background: Acceptance and wearing of complete dentures are related to adaptive behaviour of edentulous patients. However, one reason that could interfere with the wearing dentures is their potential to fracture, which is still a common complication in denture rehabilitation practice. Material and methods: Two hundred and twenty-four edentulous patients rehabilitated with complete dentures from 2000 to 2005 in Araçatuba and Araraquara Dental School, University of State of São Paulo, were assessed in 2006 and 2007 to answer a questionnaire about wearing and fracture of their dentures. Statistical analysis were performed using Epi Info software and chi-squared test to compare maxillary and mandibular data (α = 0.05). Results: Almost 26% of the patients did not wear their dentures, and among the remainder, the majority wore the maxillary denture. About 30% of the dentures were fractured, with higher prevalence in the maxillary arch (p = 0.003). Conclusions: Discontinuation of wearing dentures was quite high, especially considering the treatment which was carried out in university clinics. Prevalence of fractures was also high, greater for the maxillary denture, and was one of the main reasons for non-wearing of complete dentures. © 2011 The Gerodontology Society and John Wiley & Sons A/S.
Keywords: acrylic resin; complete denture; denture fracture; denture wearing; poly (methyl methacrylate); adaptive behavior; aged; attitude to health; Brazil; comparative study; complete lower denture; complete upper denture; cross-sectional study; dental surgery; denture; falling; female; human; male; mastication; middle aged; mouth disease; patient attitude; psychological aspect; statistics; stomatitis; tooth prosthesis; Accidental Falls; Adaptation, Psychological; Aged; Aged, 80 and over; Attitude to Health; Bite Force; Cross-Sectional Studies; Dental Restoration Failure; Denture Retention; Denture, Complete; Denture, Complete, Lower; Denture, Complete, Upper; Female; Humans; Male; Middle Aged; Mouth, Edentulous; Patient Acceptance of Health Care; Stomatitis, Denture; Tooth, Artificial